The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1007/s10096-019-03478-2
|View full text |Cite
|
Sign up to set email alerts
|

Serum albumin is a strong predictor of sepsis outcome in elderly patients

Abstract: Serum albumin is a strong predictor of sepsis outcome in elderly patients

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
60
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 18 publications
6
60
2
3
Order By: Relevance
“…Our research suggests that both lower maximum and minimum albumin indicate an increased hospital mortality. This result is also supported by several previous studies [ 28 30 ]. As the most common protein in the human body, serum albumin has important physiological functions such as maintaining plasma osmotic pressure, buffering function and binding capacity.…”
Section: Discussionsupporting
confidence: 92%
“…Our research suggests that both lower maximum and minimum albumin indicate an increased hospital mortality. This result is also supported by several previous studies [ 28 30 ]. As the most common protein in the human body, serum albumin has important physiological functions such as maintaining plasma osmotic pressure, buffering function and binding capacity.…”
Section: Discussionsupporting
confidence: 92%
“…Serum albumin level is a common indicator for assessing a patient’s nutritional status, organ function, and comorbidity. The inflammatory state resulting from bacterial infection, which leads to the production of IL-1, TNF, and other cell mediators, can interfere with liver albumin synthesis, resulting in hypoalbuminemia [30]. There is currently a lack of literature on the relationship between mortality and serum albumin level in patients with E. coli infections.…”
Section: Discussionmentioning
confidence: 99%
“…This means that lower albumin levels correlate with severe systemic inflammation and organ failure [14]. Moreover, several studies demonstrated that low albumin levels correlated with adverse clinical outcomes [11, 15].…”
Section: Introductionmentioning
confidence: 99%